Assessing the accuracy of improved force‐matched water models derived from Ab initio molecular dynamics simulations. Issue 19 (27th May 2016) - Köster, Andreas; Spura, Thomas; Rutkai, Gábor; Kessler, Jan; Wiebeler, Hendrik; Vrabec, Jadran; Kühne, Thomas D.
Abstract : The accuracy of water models derived from ab initio molecular dynamics simulations by means on an improved force‐matching scheme is assessed for various thermodynamic, transport, and structural properties. It is found that although the resulting force‐matched water models are typically less accurate than fully empirical force fields in predicting thermodynamic properties, they are nevertheless much more accurate than generally appreciated in reproducing the structure of liquid water and in fact superseding most of the commonly used empirical water models. This development demonstrates the feasibility to routinely parametrize computationally efficient yet predictive potential energy functions based on accurate ab initio molecular dynamics simulations for a large variety of different systems. © 2016 Wiley Periodicals, Inc. Abstract : The accuracy of water models derived from ab initio molecular dynamics simulations by means of an improved force‐matching scheme is assessed for a large variety of different thermodynamic, transport and structural properties. It is found that although the resulting force‐matched water models are typically less accurate than fully empirical force fields in predicting thermodynamic properties, they are nevertheless much more accurate than generally appreciated in reproducing the structure of liquid water.